AB1050 TOCILIZUMAB MODIFIES CLINICAL MANIFESTATIONS AND LABORATORY FEATURES OF SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS ASSOCIATED MACROPHAGE ACTIVATION SYNDROME. (June 2019) - Shimizu, Masaki; Mizuta, Mao; Yasumi, Takahiro; Iwata, Naomi; Okura, Yuka; Kinjo, Noriko; Umebayashi, Hiroaki; Kubota, Tomohiro; Nakagishi, Yasuo; Nishimura, Kenichi; Yashiro, Masato; Yasumura, Junko; et al.
Abstract : Background: Previous studies including a systematic literature review revealed clinical manifestations and laboratory features of systemic juvenile idiopathic arthritis (s-JIA) associated macrophage activation syndrome (MAS) could be modified in patients treated with tocilizumab (TCZ) 1, 2 . Objectives: To clarify whether TCZ modifies clinical manifestations and laboratory features of s-JIA associated MAS, and to assess performance of the 2016 MAS classification criteria for patients with s-JIA associated MAS while treated with TCZ in the real world. Methods: A combination of expert consensus and analysis of real patient data was conducted by a panel of 15 pediatric rheumatologists. Clinical manifestations and laboratory features of s-JIA associated MAS at the MAS diagnosis in 12 patients while treated with TCZ and 18 patients not treated with TCZ were evaluated. Possible MAS was defined as having characteristic laboratory features but lack of clinical features of MAS, or atypical MAS, or early treatment that prevented fulminant MAS 3, 4 . Results: Among 12 patients while treated with TCZ, only 2 patients were diagnosed with definite MAS, and other 10 patients were diagnosed with possible MAS. On the other hand, among 18 patients not treated with TCZ, 10 patients were diagnosed with definite MAS, and other 8 patients were diagnosed with possible MAS. MAS classification criteria could classify the patients diagnosed with definite MAS while treated with TCZ as having MAS as well as the patients not treated with TCZ (100% and 100%, respectively). However, this criteria were less likely to classify the patients diagnosed with possible MAS while treated with TCZ as well as the patients not treated with TCZ (60% and 75%, respectively). Furthermore, the patients with possible MAS while treated with TCZ were less likely febrile and significantly less often had rash, and had notably lower ferritin levels (587 versus 8518 ng/ml; P=0.0021), compared to the patients with possible MAS not treated with TCZ. Other laboratory features of MAS including lower platelet counts, lower fibrinogen were more pronounced in patients treated with TCZ. Conclusion: These findings show TCZ could modify clinical manifestations and laboratory features of s-JIA associated MAS. When evaluating s-JIA patients while treated with TCZ, care must be taken to not underdiagnose MAS based on MAS classification criteria. References: [1] Shimizu M, et al. Cytokine 2012;58:287-294. [2] Sculert GS, et al. Arthritis Care Res 2018;70:409-419 [3] Grom AA, et al. Arthritis Rheumatol 2016;68:218-228. [4] Yokota S, et al. J Rheumatol 2015;42:712-722. Disclosure of Interests: Masaki Shimizu: None declared, Mao Mizuta: None declared, Takahiro Yasumi Shareholder of: Takeda, Speakers bureau: AbbVie, Novartis, CSL Behring, Naomi Iwata: None declared, Yuka Okura: None declared, Noriko Kinjo: None declared, Hiroaki Umebayashi Speakers bureau: AbbVie, Eisai, Novartis, Ono, Chugai, Tomohiro Kubota: None declared, Yasuo Nakagishi: None declared, Kenichi Nishimura: None declared, Masato Yashiro: None declared, Junko Yasumura: None declared, Hiroyuki Wakiguchi: None declared, Nami Okamoto: None declared, Masaaki Mori Grant/research support from: Tokyo Medical and Dental University (TMDU) received unrestricted research grants for Department of Lifetime Clinical Immunology from AbbVie GK, Ayumi Pharmaceutical Corporation, Chugai Pharmaceutical Co., Ltd., CSL Behring K.K., Japan Blood Products Organization, Mitsubishi Tanabe Pharma Corporation, Nippon Kayaku Co., Ltd., Ono Pharmaceutical Co., Ltd., Towa Pharmaceutical Co., Ltd., UCB Japan Co. Ltd.